PLANT ORNAMENT IN POTTERY ART OF UZBEKISTAN - Ataeva Nargiza Rustamovna; Panaeva Malokhat Muminovna (Web of Journals Publishing, 2025)
This article examines the artistic features of the plant ornament of traditional ceramics of Uzbekistan. It also analyzes the historical development of traditional ceramics of Uzbekistan.
Keywords: Pattern, geometric, plant, zoomorphic, anthropomorphic. Tradition.